2021
DOI: 10.1002/ente.202100418
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cyclic Stability of Sulfur Electrode by a Li‐Nafion‐Supported Encapsulated Configuration

Abstract: Lithium–sulfur batteries are deemed to have the opportunity to replace lithium‐ion batteries because of their high energy density. Nonetheless, the shuttling of soluble long‐chain polysulfides severely deteriorates the cyclic performances of the batteries. Herein, an encapsulated sulfur electrode to tackle the shuttle effect is designed. This high‐performance electrode is fabricated by encapsulating the active sulfur inside a sealing configuration composed of lithiated Nafion (Li‐Nafion), carbon black (BP2000)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20][21][22][23] Our previous studies have systematically probed the impact of the coverage percentage of the interlayer on the sulfur electrode. [24,25] These investigations demonstrated that the cyclic stability of the battery would be enhanced as the coverage percentage rose.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18][19][20][21][22][23] Our previous studies have systematically probed the impact of the coverage percentage of the interlayer on the sulfur electrode. [24,25] These investigations demonstrated that the cyclic stability of the battery would be enhanced as the coverage percentage rose.…”
Section: Introductionmentioning
confidence: 93%
“…It is widely verified that the pathway through which soluble polysulfides migrate to the anode can be extremely obstructed by an interlayer, thus remarkably reducing the shuttle effect [11–23] . Our previous studies have systematically probed the impact of the coverage percentage of the interlayer on the sulfur electrode [24,25] . These investigations demonstrated that the cyclic stability of the battery would be enhanced as the coverage percentage rose.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated the improvement of LSB performance by exploiting Li-Nafion as a coating layer on standard polymer separators, 30 or cast over positive 31,32 or negative electrodes, 33 as a free-standing membrane 34–37 and as a constituent of the composite positive electrodes. 34 Li-Nafion is typically used in LSBs once swollen in low boiling point ether mixtures of 1,3-dioxolane (DOL) and 1,2-dimethoxyethane (DME) to improve adhesion and reduce interfacial resistances.…”
Section: Introductionmentioning
confidence: 99%
“…29 Aer ion exchange of H + with Li + , the lithiated Naon (Li-Naon) membrane swollen with specic organic solvents possesses an ionic conductivity of 4 × 10 −4 S cm −1 at room temperature, 26 which is much larger than that of many previously reported monoionically conductive polymer electrolytes. Several studies demonstrated the improvement of LSB performance by exploiting Li-Naon as a coating layer on standard polymer separators, 30 or cast over positive 31,32 or negative electrodes, 33 as a free-standing membrane [34][35][36][37] and as a constituent of the composite positive electrodes. 34 Li-Naon is typically used in LSBs once swollen in low boiling point ether mixtures of 1,3-dioxolane (DOL) and 1,2-dimethoxyethane (DME) to improve adhesion and reduce interfacial resistances.…”
Section: Introductionmentioning
confidence: 99%